Porous boron nitride nanofibers as effective nanofillers for poly(vinyl alcohol) composite hydrogels with excellent self-healing performances. Issue 4 (5th January 2022) - Gao, Xiangqian; Deng, Tiantian; Huang, Xindi; Yu, Mengmeng; Li, Danyang; Lin, Jing; Yu, Chao; Tang, Chengchun; Huang, Yang
Abstract : New composite hydrogels with excellent self-healing properties were prepared by combining poly(vinyl alcohol) (PVA) and boron nitride nanofibers (BNNFs) via a facile one-pot assembly method. Abstract : New composite hydrogels with excellent self-healing properties were prepared by combining poly(vinyl alcohol) (PVA) and boron nitride nanofibers (BNNFs) via a facile one-pot assembly method. One-dimensional porous BNNFs with high aspect ratio, abundant hydroxyl functional groups, especially excellent flexibility which has been first demonstrated in experiments, can act as a decent inorganic nanofillers to effectively improve the mechanical and self-healing properties of PVA hydrogels. Both the tensile and compression performances of hydrogels have been greatly improved by the trace addition of BNNFs (only ∼1.25 wt%). Compared with other BN nanofillers with spherical particles and lamellar morphologies, BNNFs with high aspect ratios and good flexibility play a unique role in the preparation of PVA composite hydrogels with cross-linked three-dimensional polymeric networks. This can be explained by the different topological structures of composite hydrogels formed. The abundant hydroxyl functional groups can form a lot of reversible hydrogen bonds with the molecular chains of PVA, so the as-prepared hydrogels have a high self-healing efficiency. The best healing efficiency of the composite hydrogels with 2.25 wt% BNNFs reaches as high as 97.31% after self-healing for 30 minutes. The good flexibility of BNNFs is beneficial to the movement of the PVA chain, which is beneficial to the self-healing process of composite hydrogels. The outstanding self-healing performance is very important for the application of composite hydrogels in the biomedical field and wearable flexible devices.